Capitalist Globalization : Consequences, Resistance, and Alternatives. - Hart-Landsberg, Martin (Monthly Review Press, 2013)
""Globalization, "" surely one of the most used and abused buzzwords of recent decades, describes a phenomenon that is typically considered to be a neutral and inevitable expansion of market forces across the planet. Nearly all economists, politicians, business leaders, and mainstream journalists view globalization as the natural result of economic development, and a beneficial one at that. But, as noted economist Martin Hart-Landsberg argues, this perception does not match the reality of globalization. The rise of transnational corporations and their global production chains was the result of.